2016
DOI: 10.5572/ajae.2016.10.4.208
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Airborne Hexavalent Chromium Concentrations in Large Industrial Complexes in Korea

Abstract: This paper reports the results of a field evaluation which used sampling and analytical methods to det ermine the levels of airborne hexavalent chromium Cr(VI) in major industrial complexes in Korea over a seven year period (20072013). Cr(VI) concentra tions were determined using cellulose filter sampling and ion chromatography analysis. In order to vali date the analytical performance of these methods, studies were also carried out to investigate data quality control (QC) parameters, such as the method detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…It is located near the Gwangyang industrial complex, which is populated by large oil refineries and petrochemical manufacturing plants [ 9 , 10 ]. A number of studies have been conducted and reported that the levels of environmental air pollution—including nitrogen dioxide (NO 2 ), carbon monoxide (CO), ozone (O 3 ), dioxins, toxic metals, volatile organic compounds (VOCs), formaldehyde, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), and particulate matter (PM)—were significantly increasing in the atmosphere, soil, and aquatic environments in these industrial complexes, which have been most affected [ 11 , 12 , 13 ]. Several studies concluded that chronic exposure to low levels of hazardous pollutants were significantly related to adverse effects on respiratory and cardiovascular systems among the residents living closer to Gwangyang and Yeosu industrial complexes in Korea [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is located near the Gwangyang industrial complex, which is populated by large oil refineries and petrochemical manufacturing plants [ 9 , 10 ]. A number of studies have been conducted and reported that the levels of environmental air pollution—including nitrogen dioxide (NO 2 ), carbon monoxide (CO), ozone (O 3 ), dioxins, toxic metals, volatile organic compounds (VOCs), formaldehyde, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), and particulate matter (PM)—were significantly increasing in the atmosphere, soil, and aquatic environments in these industrial complexes, which have been most affected [ 11 , 12 , 13 ]. Several studies concluded that chronic exposure to low levels of hazardous pollutants were significantly related to adverse effects on respiratory and cardiovascular systems among the residents living closer to Gwangyang and Yeosu industrial complexes in Korea [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extracted samples were then analyzed using ion chromatography (IC) (DX-120, Dionex, Sunnyvale, CA 94085, USA), equipped with IonPac-NG1 and IonPac-AS7 (Dionex, Sunnyvale, CA 94085, USA) as the guard and analytical columns, respectively. More details of the sampling and analysis of Cr(VI) can be found in the literature [42].…”
Section: Sampling and Analysis Of Particulate Phase Hapsmentioning
confidence: 99%
“…In particular, the mean concentration of Pb at Site A (0.55 µg/m 3 ) in the Onsan nonferrous industrial complex was found to have exceeded the NAAQS (0.5 µg/m 3 as an annual average). Furthermore, the average concentration (1.4 µg/m 3 ) of Cr(VI) at Site B in the Ulsan-Mipo industrial complex appeared to have been the highest among major industrial complexes scattered all over the country [42]. In addition to large petrochemical plants, numerous machinery and transportation equipment companies were located in the Ulsan-Mipo complex [67].…”
Section: Occurrence Of Particulate Phase Haps In Ambient Airmentioning
confidence: 99%
“…The extracted samples were then analyzed using ion chromatography (IC) (DX-120, Dionex, USA), equipped with IonPac-NG1 and IonPac-AS7 (Dionex, USA) as the guard and analytical columns, respectively [22]. More details of the sampling and analysis of Cr(VI) can be found in the literature [23].…”
Section: Determination Of Trace Elementsmentioning
confidence: 99%
“…The mean concentrations of Pb at all sites appeared to be lower than the national ambient air quality standard in Korea (annual average of 0.5 μg/m 3 ). Occupational exposure to airborne Cr(VI) is associated with increased risk of lung and nasal cancers [23]. A class of Cr and its compounds has been included in the list of HAPs in Korea since 1979.…”
Section: Occurrence Of Pahs and Heavy Metalsmentioning
confidence: 99%